2016
DOI: 10.2147/ibpc.s73246
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics and blood pressure: current insights

Abstract: Gut microbiota play a significant role in host metabolic processes, and recent metagenomic surveys have revealed that they are involved in host immune modulation and influence host development and physiology (organ development). Initially, probiotics are identified as potential therapeutics to treat gastrointestinal disorders and to revitalize the disturbed gut ecosystem. Currently, studies are exploring the potential for expanded uses of probiotics for improving the health conditions in metabolic disorders th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 95 publications
(100 reference statements)
0
34
0
Order By: Relevance
“…14 Manipulating gut microbiota using pre- and probiotics might prove a valuable adjuvant to traditional antihypertensives. A meta-analysis suggested that they may lower BP by a modest degree, with potentially greater effect when BP is elevated, multiple probiotic species are consumed, the duration is ≥8 weeks, or daily consumption is ≥1011 colony-forming units.…”
Section: Pre- and Probiotics As Possible Antihypertensive Agentsmentioning
confidence: 99%
“…14 Manipulating gut microbiota using pre- and probiotics might prove a valuable adjuvant to traditional antihypertensives. A meta-analysis suggested that they may lower BP by a modest degree, with potentially greater effect when BP is elevated, multiple probiotic species are consumed, the duration is ≥8 weeks, or daily consumption is ≥1011 colony-forming units.…”
Section: Pre- and Probiotics As Possible Antihypertensive Agentsmentioning
confidence: 99%
“…Some examples of the positive outcome from probiotics have been an improved immune system through immunoglobulin production, trigger cell-mediated immune response, and help in the treatment of gut disorders such as irritable bowel syndrome (IBS), Clostridium difficile colitis, gastric ulcers lactose intolerance, and antibiotic-associated diarrhea (AAD). Positive results from probiotics are caused by the multifactorial process related to them that results in the production of organic acids, hydrogen peroxide, bacteriocins, bacteriocin-link inhibitory substances, short-chain fatty acid (SCFA)-conjugated linoleic acid, and ϒ-amino butyric acid [8]. These can cause improvements that range from improved bone density, anxiety, hyperammonemia, and improved blood lipid profile to name a few [3].…”
Section: Probioticsmentioning
confidence: 99%
“…The more recent metagenomics studies are those that have demonstrated that probiotics are involved in host immune modulation and influence the development and physiology of organs. Therefore, they have been identified as the possible medical therapies to treat GI disorders and to restore an impaired gut ecosystem [8]. Studies have strengthened the idea of the importance of probiotics in aiding the prevention and prophylaxis of gut disorders, urogenital, and respiratory infections with their results [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been many studies found that the consumption of probiotic is useful in the treatment of lactose intolerance, immune function, cholesterol, diarrhoea, blood pressure, colon cancer, Irritable bowel syndrome, colitis, inflammation and absorption of minerals (Montalto et. al., 2006;Upadrasta and Madempudi, 2016;Levri et. al., 2005;Simons et.…”
Section: Introductionmentioning
confidence: 99%